2011
DOI: 10.1109/jsen.2010.2079326
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Based Stress-Coupled Optical Racetrack Resonators for Seismic Prospecting

Abstract: Abstract-A silicon-based stress-coupled optical racetrack resonator with a crossbeam mass is proposed to detect acceleration for seismic prospecting. Acceleration applied on the crossbeam mass can result in optical phase changes in one racetrack cycle, which leads to a resonant wavelength shift. By systematically optimizing the resonator structure and mechanical characteristics, a very large wavelength shift of 52 pm under 1 g acceleration is demonstrated by numerical simulation. The maximum frequency of input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, there is the dynamic of the process, there are values with greater convergence rate than this bound. The mean measurement frequency is calculated using (6) and the perceptual relative error is calculated with (10) The results of the calculation of (10) for all the above mentioned cases (combinations of all possible revised values of 3 reference and 4 unknown frequencies) are shown in Table I. It is shown that using a standard 1 MHz the relative error is less than the limit for the appropriate relative error for the application.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is the dynamic of the process, there are values with greater convergence rate than this bound. The mean measurement frequency is calculated using (6) and the perceptual relative error is calculated with (10) The results of the calculation of (10) for all the above mentioned cases (combinations of all possible revised values of 3 reference and 4 unknown frequencies) are shown in Table I. It is shown that using a standard 1 MHz the relative error is less than the limit for the appropriate relative error for the application.…”
Section: Applicationsmentioning
confidence: 99%
“…Other industrial applications of frequency measurement techniques and frequency domain analysis of electromechanical systems are presented in [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12. (a) [35]. The theoretical model is introduced to describe the interaction between the seismic acceleration and racetrack resonator.…”
Section: Seismic Sensingmentioning
confidence: 99%